Dear Miss Lake : a novel - Pearce, A. J. (Amanda-Jane) (Pearce, A. J. (Amanda-Jane). Emmy Lake chronicles, 2025)
"London, July 1944. After nearly five years of war, the readers of Woman's Friend magazine are relying on the support of Emmy Lake and her team more than ever. With the city under attack, the magazine staff decamps to the countryside for the summer. Determined to help the women of Britain carry on, Emmy and friends are hard at work finding new ways to inspire resilience. With her army officer husband Charles posted close to home, and best friend Bunty by her side, Emmy happily throws herself into rural life, juggling children, magazine assignments, and plans for a very important wedding. And then a call comes that means she may finally fulfill her long-held dream of becoming a war correspondent. But when disaster strikes, Emmy needs her friends, her community, and her readers more than ever. Filled with courage and compassion, a lovable cast of characters, and winning wartime details, Dear Miss Lake is an enormously uplifting testament to the power of friendship and hope"--